Association of immuno-inflammatory biomarkers with response to neoadjuvant chemotherapy and prognosis in HER2-positive breast cancer: dual-center clinical evidence - Wu, Xuanlin; Wu, Siqi; Tang, Mankai; Xie, Longgui; Liu, Jianhui; Liao, Jiexu; Wang, Jie; Yang, Huawei (Frontiers in Immunology, 2026)
PurposePeripheral blood immuno-inflammatory biomarkers (IIBs) may help predict response to neoadjuvant chemotherapy (NAC) and prognosis in HER2-positive breast cancer. This study compared the predictive value of neutrophil-to-lymphocyte ratio (NLR), monocyte-to-lymphocyte ratio (MLR), platelet-to-lymphocyte ratio (PLR), and systemic immune-inflammation index (SII) for pathological complete response (pCR) and disease-free survival (DFS).Patients and methodsA total of 224 female patients with HER2-positive invasive breast cancer who received NAC followed by surgery at two medical centers (2015–2023) were retrospectively analyzed. Baseline IIBs were calculated from complete blood counts. Receiver operating characteristic (ROC) curves identified optimal cut-offs. Logistic and Cox regression analyses combined with the least absolute shrinkage and selection operator (LASSO) method were used to determine factors associated with pCR and DFS. Subgroup analyses were performed to assess consistency across clinical and treatment variables.ResultsSII demonstrated the highest discriminatory ability among tested IIBs for predicting pCR (AUC = 0.739) and was significantly associated with longer DFS (P < 0.001). Patients with low SII had higher pCR rates and improved DFS. These associations remained stable across prespecified subgroups. Other factors related to better response included lower CA15-3/CEA levels, ≥6 NAC cycles, receipt of HER2-targeted therapy, and breast-conserving surgery.ConclusionsAmong common inflammatory indices, SII demonstrated the strongest association with treatment response and prognosis in HER2-positive breast cancer. As an inexpensive, readily available biomarker, it may assist clinical risk stratification. However, given the retrospective design and substantial heterogeneity in treatment regimens, these findings should be interpreted cautiously and validated in prospective studies.